2019
DOI: 10.1088/1361-6579/ab4a6a
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the mechanical cardiac performance during end-expiratory voluntary apnea recorded with ballistocardiography and seismocardiography

Abstract: If an explicit acknowledgment of funding is required, please ensure that it is indicated in your article. If you already have an Acknowledgments section, please check that the information there is complete and correct. Page 11 AQ8 Please check the details for any journal references that do not have a link as they may contain some incorrect information. If any journal references do not have a link, please update with correct details and supply a Crossref DOI if available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
(54 reference statements)
2
8
0
Order By: Relevance
“…We presented a device capable of computing the integral of kinetic energy of a contractile cycle recorded with microaccelerometers and gyroscopes, with the aim to provide information on the mechanical activity of the heart. We previously demonstrated the capability of this device to follow changes of cardiac contractility in different conditions as already mentioned (2,12,31,32,42). With the present investigation, we add that this device can detect an acutely failing heart of ischemic origin by providing a parameter of kinetic energy.…”
Section: Rotational Dimensionsupporting
confidence: 63%
See 3 more Smart Citations
“…We presented a device capable of computing the integral of kinetic energy of a contractile cycle recorded with microaccelerometers and gyroscopes, with the aim to provide information on the mechanical activity of the heart. We previously demonstrated the capability of this device to follow changes of cardiac contractility in different conditions as already mentioned (2,12,31,32,42). With the present investigation, we add that this device can detect an acutely failing heart of ischemic origin by providing a parameter of kinetic energy.…”
Section: Rotational Dimensionsupporting
confidence: 63%
“…As explained above, the automatic identification of P, Q, R, S, and T waves on the ECG allowed for the identification of the cardiac cycle on the SCG waveforms. By combining these reference points, the systolic and diastolic phases can also be identified (12). The present investigation reported also the different impact of AMI on systolic and diastolic SCG waveforms.…”
Section: Rotational Dimensionmentioning
confidence: 58%
See 2 more Smart Citations
“…Even though the flow protocol used to measure SV in this study did not require breath holds, other sequences conducted before this flow measurement had such requirements, which may have impacted the actual values of SV in the participants. This point is also supported by the fact that some of our previous studies showed that breath holds as short as 10 s led to large increases in in healthy subjects 44 . This research protocol was not designed for studying close correlation between the two methods, but rather to evaluate their overall agreement in evaluating cardiac adaptation, which was successfully done.…”
Section: Discussionsupporting
confidence: 56%